THE EVOLUTION OF THE ROMANIAN FRUIT-GROWING SECTOR IN A EUROPEAN CONTEXT - IULIA-ALEXANDRA OPREA; NICOLETA (ILIE) MARIN; RALUCA AVRAM; ALEXANDRA NEDELCU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2024)
t This article explores the evolution of Romania's fruit-growing sector within the broader European context. Historically, Romanian fruit cultivation has undergone significant transformations, influenced by both domestic policies and the agricultural regulations of the European Union. The study analyzes the sector's development over recent decades, highlighting key stages such as modernization efforts, changes in cultivation practices, and integration into the EU market. Additionally, the challenges faced by Romanian fruit growers are examined, including climate change, market competition, and sustainability issues. By comparing Romania's progress with that of other European countries, this article aims to provide a comprehensive understanding of the current state and future prospects of the sector in a rapidly changing agricultural landscape.